An Estimation of the Incidence of Thyroiditis Among Girls in Primary Care in Spain - Elisa Martín-Merino; Aida Moreno-Juste; Belén Castillo Cano; Mar Martín Pérez; Dolores Montero Corominas (Galenos Yayincilik, 2021)
Objective:As for other auto-immune processes, thyroiditis is monitored after vaccinations. The aim was to estimate the baseline incidence of thyroiditis among girls, before investigating papillomavirus vaccination as a potential risk factor.Methods:Observational cohort study including girls aged 9-18 years and registered between 2002-2016 in the Spanish Primary Care Database for Pharmacoepidemiological Research. Girls were followed until a thyroiditis occurred, 19 years of age, left the cohort, died, or the study ended. Anonymized records were reviewed for diagnosis confirmation (endocrine discharge letter and/or free-text comments) in a random sample. Incidence rate (IR) per 105 person years (/105 py) was estimated.Results:The cohort numbered 480,169 girls, of whom 641 had a record of thyroiditis: 346 autoimmune thyroiditis; 17 thyroiditis of other types; and 278 unspecified. Incidence of recorded thyroiditis increased with age, from 23.96 at age 9 years to 47.91 at age 14 years, and stabilized around 31.06-34.43 among girls aged 15-18 years. Of the 98 records reviewed, 60.2% were 'confirmed' cases, 32.7% 'possible' and 7.1% were discarded. After correction for discarded cases, IR=20.83 'confirmed' cases, increasing to 32.12/105 py when 'confirmed' plus 'possible' cases were included. Between 2002-2005, incidences were lower (16.28 and 20.93 cases/105 py) than in the period 2007-2016 (21.17 and 33.78 cases/105 py) for 'confirmed' and 'confirmed' plus 'possible', respectively.Conclusion:Two-thirds of the recorded thyroiditis included confirmatory evidence. The incidence of thyroiditis among girls increased with age and in the later period, and remained stable among girls aged 15-18 years.